Patterns of Nodal Metastases and Predictors of Occult Disease in HPV-Associated Oropharynx Cancer. (March 2021) - Stanford-Moore, Gaelen Britton; Ochoa, Edgar; Larson, Andrew; Han, Mary; Hoppe, Kathryn; Ryan, William R.
Objective: For human papilloma virus–associated oropharynx squamous cell carcinoma (HPV+ OPSCC), we evaluated the distribution of neck-level lymph node (LN) metastasis, based on postsurgical histopathology, and the incidence of and risk factors for occult LN metastases, as these patterns need clarification for this newer cancer subset. Study Design: Retrospective cohort study. Setting: National Cancer Database (NCDB). Methods: We analyzed 2358 patients in the NCDB with HPV+ OPSCC who underwent neck dissection (ND) from 2010 to 2015. Incidence and distribution of LN metastases were calculated for neck levels I to V. Variables associated with occult LN metastasis were assessed by multivariate logistic regression. Results: In therapeutic NDs (n = 1935), the following proportions of positive LNs were found: level I, 9.0% (n = 175); level II, 81.0% (n = 1568); level III, 29.6% (n = 573); level IV, 11.9% (n = 230); and level V, 4.9% (n = 95). In elective NDs (n = 423), occult-positive LNs were found in 35.8% (n = 152), with the following proportions by level: level I, 3.3% (n = 14); level II, 26.9% (n = 114); level III, 8.7% (n = 37); level IV, 4.0% (n = 17); and level V, 0.2% (n = 1). The presence of occult LNs was independently associated with a Charlson-Deyo score of 1 (odds ratio, 2.26; 95% CI, 1.18-4.31; P = .014) and lymphovascular invasion (odds ratio, 5.91; 95% CI, 3.21-11.18; P < .001). Occult LN metastases were not significantly associated with pT classification, primary site, or number of LNs resected. Conclusion: For HPV+ OPSCC, occult nodal disease is common. Therapeutic NDs should encompass at least levels II, III, and IV and possibly I, whereas elective NDs could possibly encompass levels II and III. Level of Evidence: 4.